Harnessing high-energy MLCT excited states for artificial photosynthesis - Cotic, Agustina Ludmila (2024)
Important fractions of the energy absorbed in natural and artificial photosynthetic schemes are dissipated via fast internal conversion processes. In contrast, chromophores that undergo internal conversion on slow timescales allow high-energy excited states to engage in bimolecular or long-range reactivity, outcompeting dissipation. This provides opportunities to improve solar energy conversion efficiencies. This review focuses on MLCT chromophores and analyzes fast and slow internal conversion processes in the form of inter-ligand electron transfer and hole reconfiguration. It discusses the current scenario, the obstacles, and the progress required to establish anti-dissipative molecular energy conversion schemes.